2013
DOI: 10.1007/s40003-013-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Assessment of Dry Matter Production and Nutritional Value of Millet Legumes Mix Fodder

Abstract: The intercropping of millet with legumes rich in protein was tested at 50, 60 and 70th day of sowing for the dry matter and its nutritional value. The seeds of cluster bean, cowpea and sesbania were inter-seeded on the same day in millet. The preliminary analysis for forage quality of mixture indicated that the practice of intercropping appeared to be more successful for achieving the required nutritional value. Apparently, the successive delay in harvesting produced more dry matter and organic matter yield wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Likewise, Rasool et al [35] also reported the higher ash content under cereal-legume intercropping systems. These above-presented results are also concordant with the earlier findings of Akhtar et al [36], Ayub et al [37], Iqbal et al [8], and Uher et al [38].…”
Section: Quality Traits and Its Yieldsupporting
confidence: 93%
“…Likewise, Rasool et al [35] also reported the higher ash content under cereal-legume intercropping systems. These above-presented results are also concordant with the earlier findings of Akhtar et al [36], Ayub et al [37], Iqbal et al [8], and Uher et al [38].…”
Section: Quality Traits and Its Yieldsupporting
confidence: 93%